Benefits of Completion 3D Angiography Associated with Contrast Enhanced Ultrasound to Assess Technical Success after EVAR. Issue 5 (May 2015) - Hertault, A.; Maurel, B.; Pontana, F.; Martin-Gonzalez, T.; Spear, R.; Sobocinski, J.; Sediri, I.; Gautier, C.; Azzaoui, R.; Rémy-Jardin, M.; Haulon, S.
<x xml:space="preserve">Abstract</x> Objectives This study evaluated a new strategy to assess technical success after standard and complex endovascular aortic repair (EVAR), combining completion contrast enhanced cone beam computed tomography (ceCBCT) and post-operative contrast enhanced ultrasound (CEUS). Methods Patients treated with bifurcated or fenestrated and branched endografts in the hybrid room during the study period were included. From December 2012 to July 2013, a completion angiogram (CA) was performed at the end of the procedure, and computed tomography angiography (CTA) before discharge (group 1). From October 2013 to April 2014, a completion ceCBCT was performed, followed by CEUS during the 30 day post-operative period (group 2). The rate of peri-operative events (type I or III endoleaks, kinks, occlusion of target vessels), need for additional procedures or early secondary procedures, total radiation exposure (mSv), and total volume of contrast medium injected were compared. Results Seventy-nine patients were included in group 1 and 54 in group 2. Peri-operative event rates were respectively 8.9% (n = 7) and 33.3% (n = 18) (p = .001). Additional procedures were performed in seven patients (8.9%) in group 1 versus 17 (31.5%) in group 2 (p = .001). Two early secondary procedures were performed in group 2 (3.7%), and three (3.8%) in group 1 (p = .978). Median radiation exposure due to CBCT was 7 Gy cm2 (5.25–8) (36%, 27%, and 9% of the total procedure exposure, respectively for bifurcated, fenestrated, and branched endografts). CEUS did not diagnose endoleaks or any adverse events not diagnosed by ceCBCT. Overall radiation and volume of contrast injected during the patient hospital stay in groups 1 and 2 were 34 (25.8–47.3) and 11 (5–20.5) mSv, and 184 (150–240) and 91 (70–132.8) mL respectively (reduction of 68% and 50%, p < .001). Conclusions Completion ceCBCT is achievable in routine practice to assess technical success after EVAR. Strategies to evaluate technical success combining ceCBCT and CEUS can reduce total in hospital radiation exposure and contrast medium volume injection.